New species of Phallus from a subtropical forest in Xishuangbanna, China - Li, Huili; Mortimer, Eter E.; Karunarathna, Samantha C.; Xu, Jianchu; Hyde, Kevin D. (Phytotaxa, 2014)
Seven collections of Phallus species were made in surveys of a subtropical forest in Xishuangbanna in Yunnan Province, China, during the wet season of 2012. Macro and micro characters, together with nrITS sequence data, were used to separate the collections into three species. Phallus mengsongensis and P. serrata are introduced as species new to science, while a further Phallus species is described, but not formally introduced, due to paucity of material. Macro and micro descriptions, colour photographs, line drawings and nrITS phylogenetic data for all three species are provided, which are discussed in relation to similar species in these genera.